ORGANIZATION OF PROTECTION AND LIFE SUPPORT OF THE POPULATION FOR EMERGENCY SITUATIONS - Qurbanova Nilufar Ravshanbekovna (Web of Journals Publishing, 2024)
This article addresses the comprehensive framework for the organization of protection and life support for populations during emergency situations. It examines various strategies and methods to ensure safety, timely evacuation, provision of basic needs, and medical assistance in times of crisis. Emphasizing preparedness, coordination among agencies, and community involvement, this paper proposes actionable recommendations to enhance emergency response effectiveness and resilience.
Keywords: Emergency preparedness, population protection, life support, crisis management, emergency response, evacuation, coordination, resilience, disaster management.